Enhancing Competitive Advantage Through Innovation and Entrepreneurial Orientation: The Importance of Product Quality - Andi Naila Quin Azisah Alisyahbana; Muh. Yahya (Pinisi Journal of Entrepreneurship Review, 2024)
This study investigates the impact of innovation and entrepreneurial orientation on competitive advantage, with a focus on product quality, in Micro, Small, and Medium Enterprises (MSMEs) within the culinary sector in Makassar City. Data were collected from culinary MSMEs through surveys and analyzed using statistical methods. The research highlights the crucial role of innovation and entrepreneurial orientation in enhancing the competitive advantage of these enterprises. The findings emphasize that focusing on improving product quality is essential for MSMEs to succeed in the highly competitive culinary market. The study's practical implications suggest that culinary MSMEs in Makassar City must continuously foster innovation, cultivate an entrepreneurial mindset, and prioritize product quality to maintain and enhance their competitive standing. By doing so, these enterprises can better navigate market challenges and position themselves effectively against competitors, ultimately driving growth and success in a dynamic market environment.